(untitled) (International Journal of Language, Literacy and Translation, 2025)
Cognitive linguistics is an interdisciplinary branch of linguistics, combining knowledge and research from cognitive science, cognitive psychology, neuropsychology, and linguistics. One of the subjects often being studied under this discipline includes a phenomenon in which a lexical tends to be followed by other lexical contiguously with the word. Hence, to analyze this phenomenon, Sinclair (1991) and Louw (1993) introduced a linguistics approach known as semantic prosody. The usage of semantic preference will form clusters of meanings that will describe the common meanings in certain lexical or phrases. Meanings that were inherited from these semantic preferences will evoke cultural connotations that can reflect the social reality of the speaker. This article will discuss the collocation importance of ‘perempuan’ and ‘wanita’, two lexical that can be translated into the exact word in English: female. A collocation analysis was conducted on a text corpus in order to see which lexical often collocates with these two lexical. The collocation meaning of ‘perempuan’ and ‘wanita’ was evaluated based on the lexical list collocated with these two lexical. The result shows that ‘perempuan’ is often used to describe the gender or sexuality of a person, while ‘wanita’ is mainly used to describe something religious. ‘Perempuan’ also has a negative value but only when collocated with negative value pronouns. This research is hoped to add some value to the previous studies of collocation meaning as well as become a pioneer for upcoming studies.